Chinesisches Tagebuch - Hahn, Thomas H. (Universitätsbibliothek Heidelberg, 1982)
Day by day account of a journey through the People's Republic of China in the winter of 1981/1982. Travel dates: December 10, 1981 to February 18, 1982. Travelers: Yennie Shen, and Thomas Hahn. The two would spend later three years studying and working in China, from 1984-87. The diary covers 17 cities and two famous mountains in ten provinces. 1981 was the first year the PRC allowed individuals to enter the country (vs. organized groups and tours). Many places were not accessible at the time, and Deng Xiaoping's reform movement hadn't yet taken hold. After the economic and ideological shock wave of the Cultural Revolution (1966-1976), the country was just now slowly reorienting itself towards an uncertain future.
Keywords: China